Advances in pancreatic cancer biomarkers - Syed Hasan; Rojymon Jacob; Upender Manne; Ravi Paluri (Frontiers Media S.A., 2019)
Biomarkers play an essential role in the management of patients with invasive cancers. Pancreatic ductal adenocarcinoma (PDC) associated with poor prognosis due to advanced presentation and limited therapeutic options. This is further complicated by absence of validated screening and predictive biomarkers for early diagnosis and precision treatments respectively. There is emerging data on biomarkers in pancreatic cancer in past two decades. So far, the CA 19-9 remains the only approved biomarker for diagnosis and response assessment but limited by low sensitivity and specificity. In this article, we aim to review current and future biomarkers that has potential serve as critical tools for early diagnostic, predictive and prognostic indications in pancreatic cancer.